Sistem Pakar Mendiagnosa Impetigo Metode Variable Centered Intelligent Rule System (VCIRS) dan Tsukamoto - Syariffuddin, Slamet (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Impetigo is a skin infection that is often found in young children and toddlers. This disease is usually characterized by redness of the face, especially in the mouth and nose accompanied by the appearance of tissue such as blood or dried feces. Impetigo is a contagious disease that makes it dangerous for young children and toddlers. Impetigo disease can be seen and felt from some of the symptoms that appear on the skin of young children and toddlers, but not many can confirm the disease experienced by young children and toddlers from these symptoms so they are often ignored until the impetigo disease damages the skin of young children and toddlers. The expert system is an artificial intelligence that can be used to obtain diagnostic results to serve as a reference. diagnosis of impetigo disease in the expert system built by the author implements the method of variable centered intelligent rule system as a method for making the rule system and Tsukamoto as a method for decision making or determining the final result.